Attitude, familiarity and religious beliefs about vaccination among health science and non-health science students in a Malaysian Public University - Elkalmi, Ramadan Mohamed Mahmod; Dyab, Eman Ali; Mohd Suhaimi, Azyyati; Blebil, Ali; Elnaem, Mohamed Hassan Abdelaziz; Jamshed, Shazia; Gajdács,, Márió (MDPI, 2021)
Abstract Vaccine hesitancy has surfaced globally within the last few decades, and the fears and misconceptions of people about vaccine safety and effectiveness have been identified as key factors for their under-utilization. The familiarity, attitudes, and religious beliefs of the public and of future healthcare practitioners regarding vaccination are extensive areas needing exploration. The present exploratory cross-sectional study was designed, planned and carried out on students enrolled in health science and non-health science courses in one of the public universities of Malaysia. A research instrument that had been formulated, validated and subjected to reliability testing was used to collect the data, which were analyzed using descriptive and inferential statistics. A response rate of 80.8% (n = 202) was obtained: the majority were female (n = 161, 79.7%), and had been vaccinated before (n = 190, 97.5%), while a mere 2% did not support vaccination for reasons pertaining to safety issues. The vaccine familiarity score was 10.79 ± 1.4, which significantly differed among the study disciplines (p < 0.001). The mean of the total attitude score was 14.95 ± 1.5, with no significant difference among demographics being noted. The mean of the total religious beliefs score was 24.29 ± 2.8 and significantly differed based on gender (p = 0.040) and study disciplines (p < 0.001). The current findings showed that the participants were familiar with vaccines and had generally positive attitudes and positive religious beliefs toward vaccination; thus, one can expect that their inclusion in immunization campaigns will generate positive outcomes of the immunization program. Although the current research reported few knowledge gaps, these may be handled with the introduction of a specialized immunization course at an undergraduate level.